After excessive teacher and faculty entitlement : expanding the space for healing and human flourishing through ideological becoming - Ratnam, Tara; Craig, Cheryl J. (Advances in research on teaching ;, 2024)
This second collection of perspectives on excessive teacher/faculty entitlement draws together authors from nine countries to address afresh the 'conundrums' affecting teaching and teacher education through the new lens afforded by the notion of excessive entitlement. After Excessive Teacher and Faculty Entitlement helps teachers/educators negotiate the living contradictions they experience in their sociocultural and institutional milieux which threaten their professional, emotional, and moral survival with the defensive shield of excessive entitlement they feel compelled to embrace. Chapters provide guidance to increase the possibilities of co-creating better learning and working environments for all to realize the commonly cherished educational and life goal of human flourishing. Besides education and teacher education practice, After Excessive Teacher and Faculty Entitlement has relevance for dealing with excessive entitlement in organizational contexts by offering new ways to view and address the problem.